Multimedia modeling : 26th International Conference, MMM 2020, Thessaloniki, Greece, January 8-11, 2019, proceedings.: 26th International Conference, MMM 2020, Thessaloniki, Greece, January 8-11, 2019, proceedings. Part II ([2020]) - Unknown
No abstract available